Correlation of Amniotic Fluid Index with Fetomaternal Outcomes - Kanwal, Munazza; Mushtaq, Qurratulain; Mustafa, Nilofer; Naqvi, Sadiqa Batool; Sheikh, Mehma Nafees; Rabea Al Hassan; Rehman, Mounazza (Indus Journal of Bioscience Research, 2025)
Background: Although abnormal amniotic fluid index (AFI) is associated with unfavorable pregnancy outcomes, its prognostic validity for the entire spectrum of AFI is still up for debate.  Ultrasound-based AFI evaluation is a rather easy and non-invasive method that can help physicians with risk assessment and prompt decision-making in environments with limited resources. Objective: To determine the correlation between AFI measured in the third trimester and Fetomaternal outcomes in singleton pregnancies. Methods: Prospective cohort of 126 antenatal women (≥36 weeks gestation) recruited at a tertiary center from November 2024 – April 2025. AFI was measured by four quadrant ultrasound and participants stratified into oligohydramnios (≤5 cm), borderline (5.1–8 cm), normal (8.1–24 cm) and polyhydramnios (>24 cm). Primary outcomes were mode of delivery, Apgar